Red rabbit - Clancy, Tom, 1947- (New York : G.P. Putnam's Sons, 2002)
In 1984, Jack Ryan must foil a Soviet plot to assassinate Pope John II.
Accelerated Reader AR
Keywords: John Paul -- II, -- Pope, -- 1920-2005 -- Assassination attempts -- Fiction; Ryan, Jack (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Americans -- England -- Fiction; Assassination -- Fiction; Popes -- Fiction; Political fiction; Suspense fiction